Estimation of modern range of fungicides and scope of their application in agriculture of Ukraine as component of state social and hygienic monitoring - Vavrinevych O.P.; Omelchuk S.T.; Bardov V.G. (Medičnì Perspektivi)
The analysis of the range of pesticides, including fungicides, authorized for use in Ukraine and the scope of their application during 1999 - 2012 years was carried out. Statistical research methods were used in the analysis, evaluation of the results was car¬ried out in terms of the rate of growth and increase. It was determined that in the range structure of pesticides, authorized for use in Ukraine the largest share accounted for herbicides. Part of the herbicides was 43,8±0,95% on average over the period from 1999 to 2012. The share of fungicides was 28,6±1,1%, insecticides - 20,3±0,78%, plant growth regulators - 7,4±0,59%. Mixed fungicides are the largest part of fungicides in the structure of the range (26,3-39,3%), the number of its had increased by 542% over 13-year period. Prior to 2003 there was a slight increase in the number of mixed fungicides, growth rate was 0-8,3% since 2006, its rate of increase has averaged 53% every 2 years. Triazoles and conazoles (14,9-31,4%), benzimidazoles, imidazoles (9,8-14,7%), carbamates, dithiocarbamates (3,1-13,8%), inorganic compounds (6,1-11,1%) containing one active ingredient in formulation were the most common among the fungicides. The growth rate of strobilurin fungicides was 900%, triazoles – 550%, benzimidazoles, imidazoles – 400%, inorganic compounds – 243%, aniline-pyrimidines – 200%, pyrimidines, pyridines, pyrroles – 67%, dithiocarbamic and carbamic acid derivatives – 50%, phthalimides, phenylsulfamides, amides – 43%.